A descriptive study of complications following vaginal surgeries for genital prolapse - RL, Jayavani; S, Kalaranjini; Muthalu, Arunkumar; Latha Chaturvedula; Habeebullah Syed (Asian Journal of Medical Sciences, 2022)
Background: Pelvic organ prolapse is the descent of the pelvic organs into the vagina accompanied by urinary, bowel, and sexual. Many types of surgeries are done to fix the organ prolapse. Aims and Objectives: This study aims to study the intra-operative and immediate post-operative complications in patients undergoing surgery for genital prolapse. The study also aims to follow the patients for a period of 1 year evaluate the possible morbidity during the period and also assess the factors which contribute to this morbidity. Materials and Methods: The present study was conducted in a tertiary care hospital in Puducherry among 121 patients who were admitted in the department of obstetrics and gynecology for genital prolapse. It was intended to study the intraoperative, early post-operative, and long-term complications among these patients who underwent vaginal surgeries for genital prolapse. Results: Ward Mayo’s operation was done in the age group of 45–50 years and Manchester repair was done in the age group of 30–35 years. Patients who underwent Ward Mayo’s procedure had a parity of 3.5. Nearly 25% of patients had a parity of 25. There was a significant difference in operating time when surgeries were done by consultants when compared to senior residents (P=0.002) but there was no significant difference in blood loss (P=0.070). A significant increase in blood loss and operating time was noted when vaginal hysterectomy was combined with both anterior and posterior repair. In cases of complications, it was prolonged. Backache (4.95%, 4.13%, and 4.13) and psychological problems (4.13%. 6.61%, and 6.61%) after 6 weeks, 6 months, and 1 year, respectively, were common long-term complications that could be attributed to decreased awareness among our women. Conclusion: It is concluded from the study that vaginal surgeries for genital prolapse have lesser complications both intra-operatively and during the post-operative period. The patient’s characteristics such as age, parity, other illnesses, and surgical details such as choice of the operation, experience of the surgeon, additional procedures performed, blood loss, and antibiotic usage influence the morbidities associated with the surgery.